Effects of Improving Glycemic Control with Insulin on Leptin, Adiponectin, Ghrelin and Neuropeptidey Levels in Patients with Type 2 Diabetes Mellitus: a Pilot Study - Katsiki, Niki (Bentham Open, 2011)
OBJECTIVE: Insulin therapy is associated with weight gain in patients with type 2 diabetes mellitus (T2DM). Several peptides are implicated in appetite control. We evaluated the effects of insulin-induced improved glycaemic control on leptin, adiponectin, ghrelin, neuropeptide Y (NPY) levels and patient characteristics. METHOD: Consecutive T2DM patients (n = 90) were divided into 2 groups: Group A: 45 insulin-naïve uncontrolled (glycosylated haemoglobin A(1c); HbA(1c )>7%) patients on oral hypoglycaemic agents (OHAs) who converted to insulin monotherapy. Group B: 45 well-controlled (HbA(1c )<7%) patients on OHAs. Both groups were monitored at baseline, 3 and 6 months. Males and females were analyzed separately because some hormone levels differ between genders. RESULTS: In both genders, insulin therapy (Group A) was associated with significant (p = 0.003 to <0.001) increases in weight, body mass index and leptin levels and significant decreases in glucose, HbA(1c) and NPY levels. In male insulin-treated patients a significant increase in adiponectin levels (p = 0.008) was observed. There were significant correlations (p = 0.016 to <0.001) between leptin levels, waist circumference and body fat in all patient groups, except group B males. CONCLUSION: Changes in leptin, adiponectin and NPY levels may occur after insulin-induced improved glycaemic control. These changes may be influenced by gender, weight, body fat and HbA(1c).